Injectable Fillers for Volume Replacement in the Aging Face - Greco, Timothy M.; Antunes, Marcelo B.; Yellin, Seth A. (Facial Plastic Surgery, 2012)
In recent years, there has been a better understanding of the aging process. In addition to changes occurring in the skin envelope, significant changes occur in the subcutaneous fat and craniofacial skeleton. This has led to a paradigm shift in the therapeutic approach to facial rejuvenation. Along with soft tissue repositioning, volumizing the aging face has been found to optimize the result and achieve a more natural appearance. Early in the aging process, when there has not been a significant change to the face requiring surgical intervention, fillers alone can provide minimally invasive facial rejuvenation through volumizing. Multiple injectable soft tissue fillers and biostimulators are currently available to provide facial volume such as hyaluronic acid, calcium hydroxylapatite, poly-l-lactic acid, polymethyl methacrylate, and silicone. A discussion of the morphological changes seen in the aging face, the properties of these products, and key technical concepts will be highlighted to permit optimum results when performing facial volumizing of the upper, middle, and lower thirds of the face. These fillers can act as a dress rehearsal for these patients considering structural fat grafting.
Keywords: aging face; volume loss; hyaluronic acid; calcium hydroxylapatite; poly-l-lactic acid